UPAYA MENINGKATKAN KESADARAN REMAJA AKAN KESETARAAN GENDER BERDASARKAN MORAL KRISTIANI - Bramantyo, Rafael Dimas; Prodeita, Theresia Vita (CREDENDUM: Jurnal Pendidikan Agama, 2023)
Discrimination and subordination of women in society are still common. Women experience injustice in various fields of life due to the patriarchal culture adopted by society. The gender equality movement is needed to fight for equal relations between men and women. This study aims to analyze the gender equality movement in Asia, especially in Indonesia based on Christian morals. The author uses a library research method by examining the main book "Lahir dari Rahim" by Mutiara Andalas, SJ as a starting point for writing. The author then developed the idea of the book supported by teachings from the Bible, Church Social Teachings, and various scientific journals related to the gender equality movement. In this literature research, the author finds that one of the efforts to achieve gender equality is that everyone needs to see each other as "the other self" in society. The existence of good cooperation between men and women can produce equal relations in society. The author also finds that faith education makes an important contribution to the effort to realize gender equality. Faith education related to gender equality is in line with Christian morality which emphasizes respect for the dignity of the human person, both men, and women. This faith education needs to be strengthened during adolescence because they are in the stage of searching for their identity, role, and position amid church and community life. Therefore, the author proposes a catechesis program to gradually increase adolescents' awareness of gender equality until they can make a real movement or attitude to realize gender equality in the Church and society.